FORMATION CONDITIONS OF GREISENS AT THE KOKLANOVSKOE W-MO DEPOSIT (KURGAN DISTRICT) - M.V. Zabotina; E.E. Palenova; A.M. Yuminov (Минералогия)
Wolfram and molybdenum ore at Koklanovka deposit relates with greisen which developed on granite and wall apobasitic amphibole-biotite schists and skarnes. Insignificant Au mineralisation is determined at aposerpentinite listvenite and beresite-like metasomatites. Method of thermobarogeochemistry was used for detecting of genetic relation between the greisen and carbonate-bearing metasomatites. It was obtained that greisen was formed with carbon-dioxide Cl-K-Ca solution, possible NaF, KF и NaHCO3 admixture and variable salt concentration under 225–465 °С and ~1.1 kBar. Taking into account our earlier obtained PTV data for listvenite it was revealed, that greisen and listvenite can be formed as the result of evolution of the same fluid under decreasing of temperature. Depletion of F and CO3 2- enrichment lead to post greisen carbonate association forming. Schist with marble and metaultrabasite lenses are supposed as Ca and Mg sources.